Inter-muscular coherence in speed skaters with skater's cramp - Nijenhuis, B.; Tijssen, M. A. J.; van Zutphen, T.; van der Eb, J.; Otten, E.; Elting, J. W. (Parkinsonism & Related Disorders, 2023)
Introduction Skater's cramp is a career-ending movement disorder in expert speed skaters noted to be a likely task-specific dystonia. In other movement disorders, including task-specific dystonia, studies have found evidence of central dysregulation expressed as higher inter-muscular coherence. We looked at whether inter-muscular coherence was higher in affected skaters as a possible indicator that it is centrally driven, and by extension further evidence it is a task-specific dystonia.